Effect of NaCl on growth germination and soluble sugars content in Chenopodium quinoa Willd. seeds - Prado, Fernando Eduardo (2000)
The influence of NaCl on germination rate, growth, and soluble sugar content in quinoa (Chenopodium quinoa Willd.) seeds and seedling components (cotyledons and embryonic axes) during early germination was investigated. Under saline conditions germination decreased markedly. The delay in germination rate was not linear. In presence of 0.4 M NaCl, the percentage of germination was only 14% after 14 h, whereas the control at the same time reached maximum germination (87%). The percentage of aborted seeds after 14 h in NaCl was lower than in distilled water (7% and 16%, respectively). A high percentage (67%) of the ungerminated seeds from saline treatment germinated after washing with distilled water. Fresh weight was reduced by salinity in both embryonic axes and cotyledons. The highest increase in fresh weight was observed in embryonic axes, where an increase up to 3-fold higher occurred in distilled water than in saline conditions after 10 h of development. The water content of embryonic axes in distilled water increased considerably for the first 10 h, then remained constant thereafter. In saline conditions, no significant changes were observed in water content. NaCl did not strongly inhibit dry mass production in either embryonic axes or cotyledons. Total soluble sugar content increased markedly in distilled water, peaking after 6 h for both embryonic axes and cotyledons. Reduced glucose and fructose contents were found in embryonic axes in the presence of NaCl. However, in the cotyledons, the glucose and fructose contents did not differ significantly. Levels of sucrose were higher in NaCl-treated cotyledons than in control seeds. The relationships between germination, water content, seedling growth, and soluble sugar content in relation to salt stress are discussed.